Policy Formulation of The Rechterlijk Pardon Concept (Judge's Forgiveness) In Traffic Accident Criminal Cases - Nilvany Hardicky; Riadi Asra Rahmad; Heni Susanti (Dinasti Research, 2024)
The concept of Rechterlijk Pardon (Judge's Forgiveness) is a new concept that was born in the RKUHP, where Judges are given the authority to forgive perpetrators of criminal acts even if they are proven guilty. The aim of this research is to find out how the concept of Rechterlijk Pardon (Judge's Forgiveness) is used in criminal traffic accidents. The main problem in this research is how to apply the Rechterlijk Pardon (Judge's Forgiveness) concept in traffic accident criminal cases and what are the weaknesses of the Rechterlijk Pardon (Judge's Forgiveness) concept in the perspective of Indonesian criminal law. The research method used is normative juridical with techniques for searching legal materials by means of library studies, documentation studies and the internet. From the results of this research, it can be concluded that the concept of Rechterlijk Pardon (Judge's Forgiveness) can be applied to traffic accident cases if it meets the requirements based on the provisions of RKUHP Article 54 paragraph (2)